Potential Comparison of Anti-inflammatory Activities of Quercetin and Diclofenac Mouthwash Formulations - Anu Iswarya Jaisankar; Jishnu Krishna Kumar (Editorial Ciencias Médicas, 2023)
Introduction: Periodontitis is a pandemic, with about 14% of people worldwide already suffering from severe periodontitis. Early intervention in the disease could probably reduce its progression and eliminate the need for the extraction of affected teeth. Quercetin is a probable candidate as it has exemplary anti-inflammatory properties. The presence of phenolic hydroxyl groups in them greatly contributes to their antioxidant and anti-inflammatory activities. Objectives: The study introduces the formulation of Quercetin mouthwash and assesses its anti-inflammatory properties in comparison to Diclofenac sodium. Methods: Quercetin mouthwash was prepared using a commercially procured bioactive agent.  One standard nonsteroidal anti-inflammatory drug, Diclofenac was used as a reference drug. The percentage inhibition of protein denaturation was calculated and its anti-inflammatory properties were evaluated through Bovine Serum Albumin Assay and Egg Albumin Assay. Results: Quercetin mouthwash showed parallel anti-inflammatory properties and showed a proportionate increase in anti-inflammatory properties with the increase in the concentration of the mouthwash. Comparable inhibition of protein denaturation at 10µl and 50µl concentrations with a proportionate variation of 1% (p>0.05) to the control in Egg Albumin Assay and 47% and 83% denaturation at 10µl and 50µl of Bovine Serum Albumin Assay were observed. Conclusion: Quercetin mouthwash has shown significant anti-inflammatory activity and hence is considered a potent anti-inflammatory agent comparable to Diclofenac sodium. It is found to be a suitable agent as an oral formulation for reducing the progression of inflammatory conditions.